Epiploic appendagitis with acute pyelonephritis: a case report - Dhanawat, Aditya; Mahali, Ashim Kumar; Mohanty, Lalatendu; Mohanty, Ambika Prasad (International Journal of Advances in Medicine, 2019)
Coexistence of acute epiploic appendagitis with acute pyelonephritis is a rare occurrence. Present study report here a case of a 36-year-old male with a past history of appendectomy presenting with complaints of pain abdomen, nausea, increased frequency of micturition and dysuria. On examination, there was tenderness and guarding in the left iliac fossa. CECT abdomen revealed resolving acute epiploic appendagitis with acute pyelonephritis. He was managed conservatively with antibiotics and anti-inflammatory agents to which he responded. Thus, epiploic appendagitis is a benign self-limiting condition which when diagnosed early prevents unnecessary surgical interventions.